Determinants of Rotavirus Vaccine Acceptance in an Area of Southern Italy with Low Vaccination Coverage: A Case-Control Study by the Health Belief Model Questionnaire - Davide Anzà; Massimiliano Esposito; Giorgio Bertolazzi; Alessandra Fallucca; Carlo Genovese; Gabriele Maniscalco; Andrea D. Praticò; Tiziana Scarpaci; Ermanno Vitale; Vincenzo Restivo (Vaccines)
Background/Objectives: Rotavirus (RV) is the primary cause of gastroenteritis in children worldwide, contributing significantly to morbidity and mortality, particularly among children under five years of age. The introduction of Rotavirus vaccines (RVV) has markedly reduced RV-related childhood deaths, especially in Europe, where substantial reductions in hospitalizations and disease prevalence have been observed. Despite these advances, RVV uptake in Italy remains below the desired targets, with notable regional disparities. In Sicily, vaccination rates have fluctuated, with current coverage failing to meet national goals. Safety concerns and insufficient parental awareness are major barriers to RVV acceptance. Methods: This case-control study was conducted in Southern Italy to identify factors influencing parental acceptance of RVV. Data were collected from parents using a structured questionnaire that assessed socio-demographic factors, vaccine knowledge, and attitudes based on the Health Belief Model (HBM). Results: Overall, 226 parents were enrolled. Higher perceived benefit of RVV was significantly associated with increased vaccine adherence (Odds Ratio = 13.65; 95% Confidence Interval = 6.88–27.09; p < 0.001). Conclusions: These results highlight the need for targeted interventions to improve vaccine coverage and address regional and socio-economic barriers to RVV acceptance. Furthermore, tailored educational campaigns and univocal information from healthcare providers could play pivotal roles in achieving higher vaccine uptake.